EVALUASI KESESUAIAN LAHAN TANAMAN PADI DAN BUAH-BUAHAN BERDASARKAN AGROEKOSISTEM DAN AGROEKONOMI DI DESA TANGGUWISIA DAN JOANYAR, KECAMATAN SERIRIT, KABUPATEN BULELENG, BALI. - Ditamulia Slamet Utama (Agriculture Faculty of Flores University, 2011)
Agroecosystem and agroeconomic evaluation of land suitability for fruit and rice agriculture in Tangguwisia and Joanyar Village, Seririt District, Bali, Indonesia. This research was conducted in the Tangguwisia Village and Joanyar Village, Seririt District, Buleleng Regency, Bali, from January to April 2011. The goals of this study were to determine the suitability of land-based agroecosystems and agroeconomies for rice and fruit crops from an agroeconomic perspective and at the level of the subclass, to understand the characteristics and qualities of the land that allow for increased production of rice and fruits and to create thematic maps of land suitability for rice plant, banana, mango, rambutan, durian, and grape in the agriculturally viable area. Land suitability was evaluated in several stages. First, a preparation phase was followed by the classification of land units (S1, S2, S3 and N). Agroecosystems with extremely agriculturally suitable soil were labelled (S1), systems with reasonably suitable soil were labelled (S2), systems with marginally suitable soil were labelled (S3) and systems considered completely unsuitable for agriculture were labelled (N). Sample points were determined and field surveys were conducted followed by soil analysis and data collection. This data was used to determine agroeconomic and agroecosystem suitability, and to make land-use planning recommendations, all of which culminated in the production of a land suitability map. Existing rice agroecosystems S2, S3 and N were found to be suitable for rice, with slope and texture as limiting factors. Land sections S3 and N were found to be suitable for bananas, with rainfall, dry season length, texture, slope and erosion as limiting factors. Land sections S2, S3 and N were found to be suitable for mango agriculture with rainfall, texture, slope, surface rock, and erosion as limiting, banana, mango, rambutan, and durian). S1 was found to be most suitable to the growing of grapes factors. Rambutan and durian cultivation was found to be best suited to the conditions in land unit N, with rainfall and texture as limiting factors. Vines were found to be suitable in section S2, S3 and N, with dry season length, texture, drainage, slope and erosion as limiting factors. Land units S1 and S2 were found to be suitable to the widest variety of crops (rice).